Numerical treatment on one-dimensional hyperbolic telegraph equation by the method of line-group preserving scheme - Hashemi, M. S.; İnç, Mustafa; Karatas, E.; Darvishi, E. (Springer Heidelberg, 2019)
.In the present paper, we introduce a powerful geometric numerical method for the non-homogenous one-dimensional telegraph equation (TE). A combination of semi-discretization and geometric integrator, group preserving scheme (GPS), is offered to obtain the numerical solutions. The stability analysis and convergence of the utilized method are investigated successfully. Power and accuracy of proposed method have been confirmed by some numerical experiments done for the TE.
Keywords: Geometric Approach; Interpolation